Práctica de enseñanza de Lenguaje en Educación General Básica, análisis de caso en el Primer año en el Centro Educativo Mario Cobo Barona del Cantón Cayambe. - Ulcuango Achina, Elva Lastenia (2016)
This ethnographic research needs to share and systematize experiences of teaching practices in the first years of basic education, describing compliance with the curriculum of current education, the implementation of appropriate strategies and methods to progressivity is encouraged language development, verbal and nonverbal communication. a tab observation class of the day and an interview with the teaching of the first year of basic general education Intercultural Bilingual Community Education Center Mario Cobo Barona, describing the educational process used by was applied; planning, implementation of the process of teaching and learning, organization of the school day, evaluation strategy, the teacher-student interaction and types of academic tasks. Visible the pedagogical practices implemented by the teacher inside and outside the classroom to strengthen the skills development of language and communication, stimulation of the senses, the previous knowledge of students, flexibility and creativity to interact with students in a collective and participatory space. At the end of the investigation it is considered a personal and institutional challenges have professional teachers that promote intercultural teaching practices for the teaching and learning of language and communication in the mother tongue Kichwa, as it is a means to promote intercultural school methodologies for conservation and assessment of the mother tongue in the community and territorial relations Kayambi Pueblo.